2018
DOI: 10.28932/jmh.v2i1.745
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Features of Moringa oleifera Leaves as Anticancer

Abstract: Cancer is a disease that can threaten human life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…cytotoxicity based on DNA damage leading to an apoptosis, inhibition of angiogenesis, and interactions with topoisomerase (Carocho & Ferreira, 2013). Edwinanto et al (2018) indicated that the flavonoids (quercetin, kaempferol and myricetin) found in Moringa leaves can induce apoptosis through intrinsic pathways by inhibition of mitogenactivated protein kinase (MAPK), extracellular-signal-regulated kinase 1/2 (ERK 1/2), c-Jun N-terminal protein kinase 1 (JNK), and protein kinase C (PKC). Other authors (Tiloke et al, 2013) found Moringa leaves to be a potential source of antitumor agents, especially due to the presence of niaziminin, a thiocarbamate, that exhibits inhibition of tumor-promoter induced Epstein-Barr virus activation.…”
Section: Bioactive Properties Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…cytotoxicity based on DNA damage leading to an apoptosis, inhibition of angiogenesis, and interactions with topoisomerase (Carocho & Ferreira, 2013). Edwinanto et al (2018) indicated that the flavonoids (quercetin, kaempferol and myricetin) found in Moringa leaves can induce apoptosis through intrinsic pathways by inhibition of mitogenactivated protein kinase (MAPK), extracellular-signal-regulated kinase 1/2 (ERK 1/2), c-Jun N-terminal protein kinase 1 (JNK), and protein kinase C (PKC). Other authors (Tiloke et al, 2013) found Moringa leaves to be a potential source of antitumor agents, especially due to the presence of niaziminin, a thiocarbamate, that exhibits inhibition of tumor-promoter induced Epstein-Barr virus activation.…”
Section: Bioactive Properties Evaluationmentioning
confidence: 99%
“…Phytochemicals have been isolated from different parts of M. oleifera, such as zeatin, quercetin, sitosterol, caffeoylquinic acid, kaempferol, tannins, terpenoids, saponins, anthraquinones, and alkaloids (Nouman, Anwar, Gull, Newton, & Rosa, 2016;Upadhyay, Yadav, Mishra, Sharma, & Purohit, 2015). Anti-cancerous agents, like glucosinolates, isothiocyanates, glycoside compounds, and glycerol-1-9-octadecanoate have been reported to exercise an effective action on cancer cell lines, during the different stages of cancer evolution (Edwinanto, Septiadi, Nurfazriah, Anastasya, & Pranata, 2018;Tiloke, Phulukdaree, & Chuturgoon, 2013). Leaves of M. oleifera have a low caloric value and can be used in a healthy diet.…”
Section: Introductionmentioning
confidence: 99%
“…Dried Moringa leaf has high nutrient density, which is 7 times of the vitamin C of oranges, 17 times of the calcium of milk, 10 times of the vitamin A of carrots, 9 times of the protein of yogurt, 15 times of the potassium of bananas, and 25 times of the iron of spinach (Koul and Chase 2015). Its antioxidant content is relatively high, especially the one from the flavonoid group (Muhammad et al 2016;Edwinanto et al 2018;Lin et al 2018), even 3 times that of other vegetables (Pakade et al 2013). Together with its content of sterol compounds and other diverse compounds, this plant can serve also as a functional food and a medicinal plant.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, drumstick plants also contained various bioactive compounds that have pharmaceutical functions such as tannins, saponins, alkaloids, flavonoids, glycosides, and reducing sugars (Isitua et al 2015). The most common bioactive compounds possessed by drumstick is flavonoid (Lin et al 2018) in the form of quercetin, kaempferol, (Muhammad et al 2016;Lin et al 2018) and myricetin (Edwinanto et al 2018) with a concentration of three times more than other vegetables such as Cabbage (Brassica oleracea), Spinach (Amaranthus gangeticus), Peas (Pisum sativum), Cauliflower (Brassica oleracea var. botrytis), and Broccoli (Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%